New Approaches for the Treatment of Chronic Graft-Versus-Host Disease: Current Status and Future Directions - Saidu, Nathaniel Edward Bennett; Bonini, Chiara; Dickinson, Anne; Grce, Magdalena; Inngjerdingen, Marit; Koehl, Ulrike; Toubert, Antoine; Zeiser, Robert; Galimberti, Sara (Frontiers in Immunology, 2020)
Chronic graft-versus-host disease (cGvHD) is a severe complication of allogeneic hematopoietic stem cell transplantation that affects various organs leading to a reduced quality of life. The condition often requires enduring immunosuppressive therapy, which can also lead to the development of severe side effects. Several approaches including small molecule inhibitors, antibodies, cytokines and cellular therapies are now being developed for the treatment of cGvHD, and some of these therapies have been or are currently tested in clinical trials. In this review, we discuss these emerging therapies with particular emphasis on tyrosine kinase inhibitors (TKIs). TKIs are a class of compounds that inhibits tyrosine kinases, thereby preventing the dissemination of growth signals and activation of key cellular proteins that are involved in cell growth and division. Because they have been shown to inhibit key kinases in both B cells and T cells that are involved in the pathophysiology of cGvHD, TKIs present new promising therapeutic approaches. Ibrutinib, a Bruton tyrosine kinase (Btk) inhibitor, has recently been approved by the Food and Drug Administration (FDA) in the United States for the treatment of adult patients with cGvHD after failure of first-line of systemic therapy. Also, Janus Associated Kinases (JAK1 and JAK2) inhibitors, such as itacitinib (JAK1) and ruxolitinib (JAK1 and 2), are promising in the treatment of cGvHD. Herein, we present the current status and future directions of the use of these new drugs with particular spotlight on their targeting of specific intracellular signal transduction cascades important for cGvHD, in order to shed some light on their possible mode of actions.